The Effectiveness of PolyAI on Students' Academic Performance - Natalia, Putri Ajeng; Halim*, Abdul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
To prevent misuse, it is crucial to utilise Artificial Intelligence (AI) efficiently due to its growing prevalence. A chatbot is an artificial intelligence system that imitates human conversation. Chatbots can be used effectively in the field of education when used properly. This research explores the utilisation and integration of the chatbot PolyAI to enhance English language learning for students at MAN 1 Samarinda. This study aims to investigate the effectiveness of PolyAI on students academic performance. The aim was to offer fresh viewpoints that enhance the ongoing discussion on integrating artificial intelligence into education. This study utilises a quasi-experimental methodology; pre- and post-test assessments were used in a quasi-experimental research method to examine PolyAI's impact on students' academic achievement. The collected data has been analysed using the Statistical Package for the Social Sciences (SPSS) to identify the effectiveness of PolyAI on students achievement. The study found that the control group had a lower mean score and greater variation among individual scores, indicating a significant difference in data. The experimental group had a higher mean score and a smaller variation, suggesting more homogeneous and consistent data. The independent sample t-test showed a significant effect of PolyAI chatbot involvement on improving English language skills, indicating a positive effect.